Epigenetic modulation by life–style: advances in diet, exercise, and mindfulness for disease prevention and health optimization - Ostaiza-Cardenas, José; Tobar, Andrea C.; Costa, Stefany Carolina; Calero, Diana Sofia; López-Carrera, Alisson; Bermúdez, Fátima German; Orellana-Manzano, Andrea (Frontiers in Nutrition, 2025)
Socio-economic and environmental factors significantly influence health by driving epigenetic changes that alter genetic expression and impact disease prevention. Lifestyle elements such as diet, exercise, mindfulness, and environmental exposure play crucial roles in modulating these mechanisms. A systematic review of studies from the past 13 years, conducted under PRISMA guidelines, examined interventions, epigenetic outcomes, and health impacts. Mindfulness practices, particularly meditation, were found to regulate DNA methylation, reducing stress and inflammation. Dietary interventions, such as the Mediterranean and DASH diets, enhanced health biomarkers and slowed epigenetic aging through favorable DNA methylation. Physical activities, such as high-intensity interval training and hybrid training, induced epigenetic modifications, improving metabolic function, mitochondrial biogenesis, and insulin sensitivity. These findings emphasize the importance of adopting modern lifestyle choices to promote health and prevent chronic diseases by influencing gene expression. Combining mindfulness, balanced diets, and regular physical activity offers substantial benefits for metabolic, cardiovascular, and mental health. However, more research is needed to understand the long-term effects of lifestyle factors on epigenetics and to develop personalized strategies that optimize disease prevention and overall wellbeing.